CME Productive and Non-productive Recurring Jets Near an Active Region AR11176 - Solanki R.; Srivastava A.K.; Dwivedi B.N. (My University, 2025)
We study the recurring jets near AR11176 during the period 2011 March 31 17:00 UT to April 1 05:00 UT using observations from the Atmospheric Imaging Assembly (AIA) on board Solar Dynamics Observatory (SDO). Mini-filaments (mini-filament1 & 2) are found at the base of these recurring jets where mini-filament1 shows the partial signature of eruption in case of Jet1–3. However, the mini-filament2 shows a complete eruption driving a full blow-out jet (Jet4). The eruption of mini-filament2 triggers C-class flare and Jet4 eruption. The eruption of Jet4 triggers a coronal mass ejection (CME). The plane-of-sky velocity of recurring jets (Jet1–4) results in 160 km s−1, 106 km s−1, 151 km s−1 and 369 km s−1. The estimated velocity of CME is 636 km s−1. The continuous magnetic flux cancellation is observed at the base of the jet productive region which could be the cause of the eruption of mini-filaments and recurring jets. In the former case, the mini-filament1 shows partial eruption and first three jets (Jet1–3) are produced, but the rate of cancellation was rather low. However, in the latter case, mini-filament2 fully erupts (perhaps because of a higher cancellation rate), and this triggers a C-class flare and a CME-productive jet. At the base of first three jets (Jet1–3), the mini-filament1 causes to push the overlying dynamic complex thin loops resulting in the reconnection and drives the jet (Jet1–3) eruptions. The formation of the plasma blobs are observed during the eruption of the first jet (Jet1). © 2020, Springer Nature B.V.